A Review of the Potential of Golden Apple Snail (Pomacea Canaliculata) as a Raw Material for Aquaculture Feed - Yuli Andriani; Rusky I. Pratama; Iis Rostini (International Journal of Scientific Multidisciplinary Research, 2023)
This review offers a overview of the golden apple snail (Pomacea canaliculata) as a potential raw material for aquaculture feed. The taxonomy, anatomy, habitat, life cycle, nutritional composition, and utilization prospects of this freshwater snail species are discussed. The golden apple snail's features, including its conical shell, distinct coloration, and unique respiratory system comprising gills and a lung, contribute to its adaptability and mobility in diverse environments. Its life cycle encompasses egg deposition, hatching, and subsequent growth stages, with reproductive maturity and lifespan influenced by environmental factors. With its significant calcium content and variable protein levels, the golden apple snail holds nutritional value. Consequently, it has gained attention as a promising ingredient for aquaculture feed due to its protein-rich meat